Effect of Varying Levels of Dietary Tryptophan on Aggression and Abnormal Behavior in Growing Pigs - Henry, Maggie; Shoveller, Anna Kate; O'Sullivan, Terri L.; Niel, Lee; Friendship, Robert (Frontiers in Veterinary Science, 2022)
Body lesions, resulting from tail-biting and ear-biting, can result in decreased health and welfare in pigs. Tryptophan, an indispensable amino acid, is needed to support protein deposition, and the synthesis of the neurotransmitter serotonin, which is important to mood, sleep-wake, and eating patterns and might play a role in aggression and abnormal behavior. Two randomized block design studies were conducted to assess the influence of varying dietary tryptophan levels on aggression and abnormal behavior in eight-week-old pigs. Six diets were formulated which met or exceeded all nutrient requirements yet differed according to the dietary tryptophan content. The first study included control (100% standardized ileal digestible tryptophan), supplemented (175% standardized ileal digestible tryptophan), and supplement-plus (250% standardized ileal digestible tryptophan) experimental diets, while the second study included deficient (80% standardized ileal digestible tryptophan), adequate control (105% standardized ileal digestible tryptophan), and extra-tryptophan (130% standardized ileal digestible tryptophan) experimental diets. Concentrations of plasma tryptophan and large neutral amino acids (tyrosine, isoleucine, leucine, valine, and phenylalanine) were analyzed using ultra-performance liquid chromatography and the tryptophan to large neutral amino acid ratio was calculated. Analysis for time active, lying, and engaging in aggressive interactions was carried out using 10-minute scan samples to determine behavioral time budgets of the pigs on different experimental diets. Pigs fed diets with supplemented tryptophan had higher concentrations of both plasma tryptophan and tryptophan to large neutral amino acid ratio compared to the pigs fed the control diet (P<0.05) in the first study, while no significant differences were detected for plasma tryptophan or the tryptophan to large neutral amino acid ratio in the second study. Diet did not have an effect (P>0.05) on weight, feed intake or behavior throughout the studies. The results suggest that an increase in dietary tryptophan relative to large neutral amino acids, fed for 29 days, impacts circulating plasma tryptophan and therefore, serotonin concentrations in the pig. Despite an increase in circulating plasma tryptophan in response to an increase in dietary tryptophan in the first study, we failed to see an impact of the dietary treatment on body, tail and ear-biting behavior under the conditions studied.